"Supersize me!" The effects of cognitive effort and goal frame on the persuasiveness of upsell offers. (19th June 2017) - Heidig, Wibke; Wentzel, Daniel; Tomczak, Torsten; Wiecek, Annika; Faltl, Martin
Abstract : Purpose: In many industries, customers are offered the opportunity to revise their initial decision in return for a superior but more expensive service option, a selling technique that is typically referred to as upselling. Drawing on the research on customers' service experience, cognitive effort, decision justification, and goal framing, the purpose of this paper is to conceptualize upselling as a two-stage decision process where the process of making the first decision (i.e. deciding on an initial service option) affects the final decision (i.e. the decision for or against the upsell offer). Design/methodology/approach: First, qualitative interviews were conducted both with customers as well as managers. Moreover, in two experimental studies, different scenarios depicted an upsell situation that is common in many service encounters. After choosing a hotel room or rental car for reservation, participants were confronted with differently framed arguments to induce a shift toward an enhanced but more costly version of the initially chosen service option. Findings: The qualitative interviews reveal that upselling is a common practice in many companies and that the manner in which the upsell is communicated has a considerable influence on its effectiveness. The first experimental study finds that the cognitive effort that customers expend in the initial choice moderates the effect of upsell messages using different goal frames. The second experimental study shows that customers are only affected by different goal frames when they feel responsible for the outcome of the final decision. Practical implications: The findings provide a number of useful guidelines for designing upselling strategies and may also be used to segment a firm's customer base. On a more general level, this research also raises managers' awareness of the sequential nature of upselling decisions and the customer's intrinsic need to justify an upsell choice. Originality/value: The studies contribute to the literature on customers' service experience and upselling strategies. Upselling is conceptualized as a two-stage process in which customers' experience in one phase influences their behavior in later stages. The underlying psychological mechanisms of this effect are also highlighted by referring to customers' need to justify service choices to themselves.